Collaborative work as a strategy to build meaningful learning collectively - Ardila Castañeda, Jorge
This document revolves around the following questions: Is it important to foster social and cooperative relationships between learners and instructors ?; Is it possible that there are still instructors who promote the traditional type of teaching, based on lectures aimed at a hearing-passive learner at SENA? To answer them, the experience of the Barrancabermeja Industrial and Technological Development Center is exposed, which uses collaborative work as a practice, implemented by instructors and apprentices, to promote meaningful learning.